2019
DOI: 10.1186/s12992-019-0451-4
|View full text |Cite
|
Sign up to set email alerts
|

The effect of community-based programs on diabetes prevention in low- and middle-income countries: a systematic review and meta-analysis

Abstract: BackgroundThe increasing prevalence of type 2 diabetes mellitus (T2DM) can have a substantial impact in low- and middle-income countries (LMICs). Community-based programs addressing diet, physical activity, and health behaviors have shown significant benefits on the prevention and management of T2DM, mainly in high-income countries. However, their effects on preventing T2DM in the at-risk population of LMICs have not been thoroughly evaluated.MethodsThe Cochrane Library (CENTRAL), MEDLINE, EMBASE and two clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 65 publications
1
46
2
Order By: Relevance
“…Community-based health programs are practical and relatively low-resource, often requiring lifestyle-changing educational programs. Previous studies suggested that community-based RCT can diagnose as well as monitor how well diabetes is controlled and improve community health habits, which ultimately reinforces the high priority given to the translation of research into new practices [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Community-based health programs are practical and relatively low-resource, often requiring lifestyle-changing educational programs. Previous studies suggested that community-based RCT can diagnose as well as monitor how well diabetes is controlled and improve community health habits, which ultimately reinforces the high priority given to the translation of research into new practices [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2019, a systematic review and meta-analysis was published reporting on the effect of community-based programs on diabetes prevention in LMICs (47). It included all RCTs published in the last 10 years (from January 2008 to March 2018), including individuals with no diabetes ≥18 years of age at risk of T2DM who lived in LMICs and evaluating community-based programs/interventions for the prevention or risk reduction of T2DM (with no pharmacological intervention) compared with no program or standard health care advice.…”
Section: Prevention Modelsmentioning
confidence: 99%
“…[84][85][86] Interventions may include key modifiable risk factors such as lifestyle, adiposity, physical inactivity, unhealthy diet (quality of staple foods) as well as pharmacological issues. 21,[87][88][89][90][91]…”
Section: Overview Of T2dmentioning
confidence: 99%